PEMBANGUNAN HUKUM ARBITRASE (POLITIK HUKUM) SEBAGAI UPAYA PENYELESAIAN SENGKETA (TINJAUAN ATAS UNDANG-UNDANG NO. 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA) - Sanjaya, Umar Haris (Jurnal Yuridis, 2015)
Nowdays every business actor as the modern businessmen would like to settled any business dispute more quickly, simply, to prevent from any risk which is rise. Government regulated the alternative dispute settlement on business field that is arbitration law. The arbitration regulation becoming a legal politic study which is interested because of the implementation of it not apply well. This research study about the Economy law and development in Indonesia regarding arbitration and how the legal politic of arbitration is perform. This study is using  descriptive methodology with juridical normative. For the conclusion is law and development in Indonesia especially arbitration is not beginning with values of societies, but taken from condition of reformation of Indonesia. However the economic law and development still need to enforce in according to make justice and prosperity especially for business actor.